Empowering Rural Communities: Insights from North-East India - Poulami Ray; Ajmer Singh; Bhagirath Das (Business, Management and Economics: Research Progress Vol. 3, 2024)
Rural development, as a whole, refers to the measures and initiatives done to raise the standard of living in rural areas, outlying towns, and isolated villages. These neighborhoods can be identified by their small population density relative to open space. Poverty, on the other hand, is a socioeconomic phenomenon in which a segment of society is unable to meet even its most basic needs. The bare necessities for humans include food, clothing, housing, education, and other necessities of life. The government (Central) has embraced the concept of cluster development to revitalize the existing small and rural enterprises. This will give the company a competitive advantage in three separate ways: through increased productivity, innovation, and the creation of new businesses. The Indian government provides total funding for NESIDS. The program provides funding for initiatives including the construction of physical infrastructure for the delivery of water, electricity, communication, and tourism. Additionally, it emphasizes social infrastructure important to health and education.